A Review on the Antimicrobial Properties of Giant Barrel Sponge- Xestospongia sp. - Hartiadi, Leonny; edny, gisella; Rebecca, Jeannifer; Sheryl, Sheryl; Crystalia, Audrey Amira (Indonesia International Institute for Life Sciences, 2020)
Indonesia sits in the heart of the largest biodiversity hotspot -Indo-Pacific region. Indonesia has access to endless resources of bioactive compounds from marine animals and plants. Marine sponges have been extensively studied over the years due to their nature of being exposed to various microorganisms. Xestospongia sp. establishes a symbiotic relationship with diverse microorganisms, leading to the synthesis of abundant bioactive resources which capable of inhibiting the growth of pathogenic bacteria. Publications from the last ten years were retrieved from PubMed and included in this review article. Bioactive compounds produced by Xestospongia sp. were effective in inhibiting gram-negative bacteria- P. aeruginosa, A. baumanii, E. coli, K. pneumoniae, P. aeruginosa, S. epidermis, S. typhi- and gram-positive bacteria -M. Intracellulare, S. aureus, S. pneumoniae, B. subtilis, V. anguaillarum. In addition, extracts were able to inhibit the growth of multidrug-resistance P. aeruginosa and methicillin-resistant S. aureus (MRSA). C. albicans, C. tropicalis, C. neofarmans, A. niger, Epidermophyton sp., M. gypseum, T. rubrum, T. mentagrophytes were susceptible to Xestospongia sp. extracts. The growth of chloroquine-resistant and susceptible strains of P. falciparum were inhibited by Xestospongia sp. with similar zones of inhibitions. The antimicrobial properties were contributed by the composition of chemically complex compounds such as phenolics, steroids and alkaloids; each of which exhibits a unique mechanism of action. The vast range of antimicrobial activity exhibited by Xestospongia sp. extracts implies their promising role in clinical settings for the treatment of infectious diseases including tuberculosis and malaria.